Influence of drugs on gap junctions in glioma cell lines and primary astrocytes in vitro - Moinfar, Zahra; Dambach, Hannes; Faustmann, Pedro M. (Frontiers in Physiology, 2014)
Gap junctions (GJs) are hemichannels on cell membrane. Once they are intercellulary connected to the neighboring cells, they build a functional syncytium which allows rapid transfer of ions and molecules between cells. This characteristic makes GJs a potential modulator in proliferation, migration and development of the cells. So far, several types of GJs are recognized on different brain cells as well as in glioma. Astrocytes, as one of the major cells that maintain neuronal homeostasis, express different types of GJs that let them communicate with neurons, oligodendrocytes and endothelial cells of the blood brain barrier; however, the main GJ in astrocytes is connexin 43. There are different cerebral diseases in which astrocyte GJs might play a role. Several drugs have been reported to modulate gap junctional communication in the brain which can consequently have beneficial or detrimental effects on the course of treatment in certain diseases. However, the exact cellular mechanism behind those pharmaceutical efficacies on GJs is not well-understood. Accordingly, how specific drugs would affect GJs and what some consequent specific brain diseases would be are the interests of the authors of this chapter. We would focus on pharmaceutical effects on GJs on astrocytes in specific diseases where GJs could possibly play a role including: 1) migraine and a novel therapy for migraine with aura, 2) neuroautoimmune diseases and immunomodulatory drugs in the treatment of demyelinating diseases of the central nervous system such as multiple sclerosis, 3) glioma and antineoplastic and anti-inflammatory agents that are used in treating brain tumors and 4) epilepsy and anticonvulsants that are widely used for seizures therapy. All of the above-mentioned therapeutic categories can possibly affect GJs expression of astrocytes and the role is discussed in the upcoming chapter.